Development of photoswitchable inhibitors for β-galactosidase. Issue 40 (28th September 2018) - Rustler, Karin; Mickert, Matthias J.; Nazet, Julian; Merkl, Rainer; Gorris, Hans H.; König, Burkhard
Abstract : Azobenzene-based light-controllable derivatives of 2-phenylethyl β-d -thiogalactoside as trans -active competitive inhibitors for β-galactosidase from Escherichia coli . Abstract : Azobenzenes are of particular interest as a photochromic scaffold for biological applications because of their high fatigue resistance, their large geometrical change between extended ( trans ) and bent ( cis ) isomer, and their diverse synthetic accessibility. Despite their wide-spread use, there is no reported photochromic inhibitor of the well-investigated enzyme β-galactosidase, which plays an important role for biochemistry and single molecule studies. Herein, we report the synthesis of photochromic competitive β-galactosidase inhibitors based on the molecular structure of 2-phenylethyl β-d -thiogalactoside (PETG) and 1-amino-1-deoxy-β-d -galactose (β-d -galactosylamine). The thermally highly stable PETG-based azobenzenes show excellent photochromic properties in polar solvents and moderate to high photostationary states (PSS). The optimized compound37 is a strong competitive inhibitior of β-galactosidase from Escherichia coli and its inhibition constant ( K i ) changes between 60 nM and 290 nM upon irradiation with light. Additional docking experiments supported the observed structure–activity relationship.